If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 11 + -4x Solving 2x = 11 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 2x + 4x = 11 + -4x + 4x Combine like terms: 2x + 4x = 6x 6x = 11 + -4x + 4x Combine like terms: -4x + 4x = 0 6x = 11 + 0 6x = 11 Divide each side by '6'. x = 1.833333333 Simplifying x = 1.833333333
| 9(3x+9)+8x-11= | | -5=9-2x | | 17=2g-3.5 | | 91381.00=32.12x+17176.23 | | 28+2(11/3)-1=22(11/3) | | 5(2+3)-4=8+27 | | 91381.00=32.12x | | 5(5x+6)+6x= | | 0.05x+0.5x=14 | | 375+n=742 | | 0.05x+0.5x= | | 19=18t+5t^2 | | 34(y-2)=26(y+2) | | 5(3x+7)-4(8x-3)= | | 1.35= | | 30x^4/(5x^(1/8)) | | 28+2x-1=22x | | 5.9(3*3x)-5.7=12 | | -x-93+9x=27 | | 4x+4y=100 | | (X/4)-(13/6)=(5x/2)-(5-6) | | 30x^2-17x-21= | | 12x+2x-74=94 | | -64+5x+4x=44 | | (13x-6)-(5x+14)=54 | | 3/5x-9=7 | | 2x-208+10x=56 | | 5t+10=5b | | -2x+8x-38=70 | | e^15=x | | 12x-3x-95=49 | | log^4(5x+1)=2 |